Dynamic changes in cellular atlases and communication patterns within yak ovaries across diverse reproductive states unveiled by single-cell analysis - Pei, Jie; Xiong, Lin; Wang, Xingdong; Guo, Shaoke; Cao, Mengli; Ding, Ziqiang; Kang, Yandong; Chu, Min; Wu, Xiaoyun; Bao, Pengjia; Guo, Xian (Frontiers in Cell and Developmental Biology, 2024)
Yaks (Bos grunniens) exhibit exceptional adaptation to the challenging high-altitude environment of the Qinghai-Tibetan plateau, making them the sole bovine species capable of thriving in such exreme conditions. Investigating the cellular and molecular characteristics of yak ovaries across different reproductive states is crucial for gaining insight into their ovarian functions. Herein, the cellular atlases of yak ovaries in different reproductive states were depicted by single-cell RNA-sequencing (scRNA-seq). The cellular atlases of the ovaries were established by identifying specific gene expression patterns of various cell types, including granulosa cells, theca cells, stromal cells, smooth muscle cells, endothelial cells, glial cell, macrophages, natural killer cells, and proliferating cells. The cellular compositions of the ovaries vary among different reproductive states. Furthermore, the granulosa cells comprise six cell subtypes, while theca cells consist of eight cell subtypes. The granulosa cells and theca cells exhibit distinct biological functions throughout different reproductive states. The two cell types were aligned along their respective pseudotime trajectories. Moreover, a cell-to-cell communication network was constructed among distinct cell types within the ovary, spanning the three reproductive states. Notably, during the estrus period, the granulosa cells demonstrated more prominent interactions with other cell types compared to the remaining reproductive states.